TAUHID SEBAGAI FONDASI KEADILAN SOSIAL DALAM PEMIKIRAN TAN MALAKA - Tohis, Reza D. (UIN Sunan Kalijaga Yogyakarta, 2020)
This paper aims to re-read Tan Malaka’s work related to the concept of social justice which he correlates with the concept of God in Islam. This needs to be done because researchers are hardly interested in Tan Malaka’s thoughts about the concept of God (Tauhid). But, in his work is found his commentary on the concept of divinity. This study uses qualitative methods with library research techniques. In analyzing the data of this study using the text critique method. Tan Malaka defines divinity as the recognition of God’s power, the Oneness of God. This confession arises based on awareness of God’s laws in the universe. Based on these laws, Tan Malaka realizes that justice means equality, and enforcement of justice means enforcement of God’s laws. In this context, religious people will always base their actions on the principles of justice, so that the concept offered by Tan Malaka can be an answer to the reality of religious life in Indonesia. This keeps monotheism away from its basic concept as a liberator. This concept also strengthens the concept of anthropocentric theology which emphasizes the cultivation of monotheism in factual reality.